2010
DOI: 10.1002/chem.201000870
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Tuning of a Carbene Center via Remote Chemical Induction, and Relevant Effects in Catalysis

Abstract: The present report develops the idea that an N-heterocyclic carbene incorporating a remote anionic functionality--here, a malonate group--as a backbone component of its heterocyclic framework, can be "post-functionalized" directly from its transition-metal complexes, upon simple addition of a variety of electrophiles interacting directly with the malonate group in the outer coordination sphere. From a palette of selected electrophilic reagents, it was thus possible to modulate the electronic donor properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(44 citation statements)
references
References 98 publications
3
40
0
1
Order By: Relevance
“…Model system and DFT calculations on the electronic structure: The lithium salt [1]·Li of the anionic carbene [1] À was chosen as the preferred model carbene system for the present study, since we had previously shown that [1]·Li is cleanly and quantitatively generated from its mesoionic precursor [1]·H with a slight excess of n-BuLi and that it is stable in solution for days at room temperature (Scheme 2). [22] When the carbene [1] À is coordinated to a metallic center in zwitterionic or anionic complexes, [22,23] its internal ligand geometry reflects the quasi-absence of electronic communication between the proximal diaminocarbene moiety NCN, a 4p e À system, and the distal malonate unit, a 6p e À system. The electronic structure of the coordinated carbene [1] À is thus best described by the average resonance form [1 d ] À , analogous with that of its precursor [1]·H, a heterocyclic member of the family of cross conjugated mesoionic betaines (CCMB).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Model system and DFT calculations on the electronic structure: The lithium salt [1]·Li of the anionic carbene [1] À was chosen as the preferred model carbene system for the present study, since we had previously shown that [1]·Li is cleanly and quantitatively generated from its mesoionic precursor [1]·H with a slight excess of n-BuLi and that it is stable in solution for days at room temperature (Scheme 2). [22] When the carbene [1] À is coordinated to a metallic center in zwitterionic or anionic complexes, [22,23] its internal ligand geometry reflects the quasi-absence of electronic communication between the proximal diaminocarbene moiety NCN, a 4p e À system, and the distal malonate unit, a 6p e À system. The electronic structure of the coordinated carbene [1] À is thus best described by the average resonance form [1 d ] À , analogous with that of its precursor [1]·H, a heterocyclic member of the family of cross conjugated mesoionic betaines (CCMB).…”
Section: Resultsmentioning
confidence: 99%
“…We have already demonstrated that the stable carbene B is capable of coordinating transition-metal centers to yield zwitterionic complexes active in catalysis. [23] Nonetheless, its structural similarities with the diamidocarbene A prompted us to explore its potential reactivity as a "free" anionic entity. Indeed, very little is known about the reactivity of anionic NHCs, [24] with the notable exception of the anionic compound C, whose electronic properties and reactivity were shown to match better with those of a phenylide-type carbanion than of a real NHC.…”
Section: Introductionmentioning
confidence: 99%
“…1). The carbenes 3 [31] and 4 [3233] originate from a conjugated ylide and a cross-conjugated mesomeric betaine, respectively. A review elucidates the interconversions of mesomeric betaines to different types of N-heterocyclic carbenes (NHC, aNHC, rNHC, MICs) and vice versa [34].…”
Section: Introductionmentioning
confidence: 99%
“…6a The effects of modifying the electronic prop--erties of NHCs ligands are known to afford important implications in the context of homogeneous catalysis and bioorganometallic chemistry, 9 and some elegant examples of fine electronic tuning of NHC ligands via remote chem--ical induction have shown to produce relevant effects in catalysis. 10 Benzo--fused nitrogen heterocycles continue to com--mand a great deal of attention because a large number of natural products and pharmaceutical compounds incor--porate these heterocyclic systems.…”
Section: Introductionmentioning
confidence: 99%